A Framework for Understanding Consumer Perceived Characteristics of Internet Banking as Predicators of its Adoption - C., Prema (Indian Journal of Marketing, 2011)
Internet banking has gained wide acceptance internationally and has become a very popular delivery platform for banking services. Advances in electronic banking technology have created novel ways of handling daily banking affairs, especially via the online banking channel. The acceptance of online banking services has been rapid in many parts of the world. The growing number of internet users and increase in financial activities online provide an opportunity for the banking industry to get a better understanding of this dynamic channel and introduce it as an additional touch point to serve the customers. In the literature, consumers' adoption of internet banking as an innovation is consistent with the theory of diffusion of innovations (Rogers 1983). The theory of diffusion of innovation has not been much applied to financial innovations, which includes internet banking. This paper presents a conceptual model for future research.